Synthesis and Anticancer Activity of New Hydrazide-hydrazoncs and Their Pd(II) Complexes - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (BENTHAM SCIENCE PUBL LTD, 2019)
Background: Hydrazones, one of the important classes of organic molecules, are pharmaceutical agents comprising -CO-NH-N=CH- group in the structure therefore and exhibiting significant biological activity. Methods: 5-Chloro-N'-[(substituted)methylidene] pyrazine-2-carbohydrazide (3a-g) and their Pd(II) complexes (4a-h) were synthesized and investigated in vitro anticancer activity on A549, Caco2 cancer and normal 3T3 fibroblast cell lines, using the MTT assay. Results: Anticancer activity screening results revealed that some compounds showed remarkable cytotoxic effect. Among them, 5-chloro-N'-[(4-hydroxyphenyl)methylidene] pyrazine-2-carbohydrazide (3c) displayed higher cytotoxic activity against A549 cancer cell line than the reference drug cisplatin. Conclusion: Compound 3c showed high cytotoxic activity against A549 cancer cell line but it showed low cytotoxic effect against normal 3T3 fibroblast cell line. Antiproliferative and antimetastatic effects of 3c were determined by the real-time monitoring of cell proliferative system (RTCA DP). The cell proliferation, metastatic and invasive activities of A549 cells were decreased due to increased concentration of 3c.
Keywords: Hydrazone; metal-complexes; anticancer activity; MTT assay; real-time monitoring; proliferative system; IN-VITRO; PROTEIN-BINDING; PLATINUM(II) COMPLEXES; CRYSTAL-STRUCTURE; DNA-BINDING; PALLADIUM(II); DERIVATIVES; LIGANDS; PROLIFERATION; ANTIOXIDANT